The Financial education: challenges and opportunities for public university students - Leyton Vite, Néstor Daniel; Izurieta Burgos, Lizbeth Katherine (Revista Internacional de Estudios en Ciencias Administrativas STRATEGOS, 2026)
Financial education has become a fundamental element in the development of economic competencies in university settings, especially in contexts characterized by the increasing complexity of financial systems. The objective of this research was to analyze the impact of financial education on the development of economic competencies in final-year students of the Faculty of Business Sciences at a public university in Ecuador. The study was conducted using a quantitative approach, with a non-experimental, descriptive-correlational design. A structured survey with a Likert scale was administered to a sample of university students, evaluating two main variables: financial education and economic competencies. Data analysis was performed using Jamovi software, including descriptive statistics, reliability analysis, Bartlett's test of sphericity, the Kaiser-Meyer-Olkin (KMO) index, exploratory factor analysis, and Pearson correlation. The results showed high levels of reliability for the instrument (α between 0.854 and 0.880), as well as adequate structural validity (KMO = 0.899; p < 0.001). Factor analysis identified a two-dimensional structure grouping operational and strategic competencies. A strong and significant positive correlation was also found between financial education and economic competencies (r = 0.728; p < 0.001), confirming that strengthening financial education contributes to the development of economic skills in students. It is concluded that financial education not only influences economic knowledge but also behavior and decision-making, thus becoming a key element for the professional development and economic well-being of university students.
Keywords: financial education; economic competencies; university students; financial decision-making